1982
DOI: 10.1037/0033-2909.92.3.701
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and interhemispheric information processing in schizophrenia.

Abstract: Over the past decade, psychopathology researchers have offered several hypotheses linking schizophrenia to specific patterns of hemispheric dysfunction. These hypotheses have, in turn, generated a substantial body of literature on intra-and interhemispheric information processing in schizophrenia. The present article reviews this literature and critically evaluates the relative merits of various hypotheses put forward to account for the findings. There appears to be little support for the notion that schizophr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
2

Year Published

1984
1984
2001
2001

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(37 citation statements)
references
References 118 publications
(141 reference statements)
3
32
2
Order By: Relevance
“…Green & Kotenko's findings have been cited as support for theories proposing the existence of left hemisphere overactivation and/or dysfunction among schizophrenic patients (e.g. Walker & McGuire, 1982). The data from this study are not generally consistent with such theories.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Green & Kotenko's findings have been cited as support for theories proposing the existence of left hemisphere overactivation and/or dysfunction among schizophrenic patients (e.g. Walker & McGuire, 1982). The data from this study are not generally consistent with such theories.…”
Section: Discussioncontrasting
confidence: 90%
“…Green & Kotenko, 1980) which reported the superiority of right ear processing of verbal stimuli in comparison with both left and binaural presentations among schizophrenic subjects. However, Walker & McGuire (1982) have suggested that this right ear superiority among schizophrenic subjects may result from their difficulty in ignoring the non-target stimuli in the right ear when the target occurs in the left ear. It should be noted here, both that Green & Kotenko used monaural stimulation and that the response requirements were much more complex than those of the study reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Opinions have differed as to how these results should be interpreted (see Walker & McGuire, 1982, for a review) but one possible explanation for abnormal degrees of lateral asymmetry in schizophrenics is that the two hemispheres have become disconnected or imperfectly coordinated. Thus normal interhemispheric control through neural excitation and inhibition across the corpus callosum is disrupted.…”
mentioning
confidence: 96%
“…In a similar vein, other investigators have suggested that memory deficits are related to information-processing limitations caused either by an inability to filter out information or by an inherent reduction in processing capacity (Lawson, McGhie, & Chapman, 1964;Nuechterlein & Dawson, 1984;Oltmans, 1978;Walker & McGuire, 1982). Such a reduction in processing capacity, it is argued, accounts for the fact that greater performance deficits are noted for tasks that involve more elaborate encoding (e.g., forming associations between concepts).…”
Section: Discussionmentioning
confidence: 91%